Phoebe: The Woman Deacon And Patron In Romans 16:1-2 - Aryanto, Antonius Galih (DISKURSUS - JURNAL FILSAFAT DAN TEOLOGI STF DRIYARKARA, 2018)
Abstract: The name “Phoebe” probably is not too familiar in the study of the New Testament before 90’s. However, in the recent study of the role of woman in the Bible in connection with the patronage system in the Greco-Roman society, Phoebe has an important role because she helps Paul in his preparation for the mission to Rome. Paul calls her as a sister, deacon, and patron. This research argues that Phoebe has a role as a benefactor and deacon within the patron-client system in the Roman society. Paul asks her to carry his letter to Rome in order that Christian community in Rome may help him for the future mission to bring the Gospel to Spain. Keywords: Phoebe, patronage, deacon, benefactor, and reciprocity. Abstrak: Nama “Febe” mungkin tidak begitu familiar dalam studi Perjanjian Baru sebelum tahun 90-an. Namun, dalam studi belakangan ini tentang peran perempuaan dalam Alkitab dalam kaitannya dengan sistem patronasi dalam masyarakat Yunani-Romawi, Febe memiliki peran penting karena dia membantu Paulus dalam persiapan misinya ke Roma. Paul menyebutnya sebagai saudari, diakon, dan pelindung. Penelitian ini hendak menunjukkan bahwa Phoebe memiliki peran sebagai donatur dan diakon dalam sistem patron-klien dalam masyarakat Romawi. Paulus memintanya untuk membawa suratnya ke Roma agar komunitas Kristen di Roma dapat menolongnya berkenaan dengan misi di masa depan yaitu mewartakan Injil ke Spanyol. Kata-kata kunci: Phoebe, patronage, deacon, donatur, dan timbal balik.